THE EFFECT OF WORK ENVIRONMENT ON TURNOVER INTENTION WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (A Study on Manufacturing Operators in Batam City) - Bambang Satriawan; Elly Rumengan; Etty Sri Wahyuni (RADJA PUBLIKA, 2026)
The high turnover rate in Batam's manufacturing industry presents a serious challenge for human resource management, particularly at the production operator level, which forms the operational backbone of factories. This study aims to analyze the effect of work environment on turnover intention with job satisfaction as an intervening variable among manufacturing operators in Batam. The research employs a quantitative approach using a survey technique with a five-point Likert-scale questionnaire. The respondents comprised 100 manufacturing operators in Batam, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results show that work environment has a positive and significant effect on job satisfaction (β = 0.612; p < 0.001), work environment has a negative and significant effect on turnover intention (β = –0.241; p = 0.012), job satisfaction has a negative and significant effect on turnover intention (β = –0.468; p < 0.001), and job satisfaction partially mediates the effect of work environment on turnover intention (β = –0.286; p < 0.001). These findings indicate that improvements in both physical and non-physical work environments can reduce operators' turnover intention through enhanced job satisfaction.